Pengaruh Sosial Ekonomi dan Kesehatan terhadap Pengeluaran Konsumsi Pangan Rumah Tangga Provinsi Jawa Tengah Tahun 2020 - Harum, Nisrina Sekar; Aini, Mifrotun; Risxi, Muhammad Alfa; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
Central Java Province is the fourth most populous province in Indonesia, so with a dense population in an area, it is important to pay attention to household consumption expenditure according to the second SDG goal, namely no hunger. The purpose of this study was to look at the distribution of household food consumption expenditures in Central Java and analyze the socio-economic and health influences on household food consumption expenditures. The data used is secondary data from the publication of the Central Java Statistics Agency in 2020. This study used multiple linear regression analysis. The results showed that the open unemployment rate and the percentage of households with proper sanitation significantly increased household food consumption expenditures. Meanwhile, the dependency ratio significantly reduces household food consumption expenditures.